Sleep habits, sleepiness and accidents among truck drivers Hábitos de sono, sonolência e acidentes em caminhoneiros - José Carlos Souza; Teresa Paiva; Rubens Reimão (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the quality of sleep, shift work, alcohol and psychostimulant drug use, and the prevalence of accidents among truck drivers. METHOD: Data were collected using a demographic questionnaire, the Epworth Sleepiness Scale (ESS) and the Pittsburgh sleep quality index (PSQI). Statistical analysis was conducted using the Student t, chi-square, Pearson and Fisher tests. RESULTS: 43.2% of the drivers drove over 16 h a day, and 2.9% worked shifts. Mean number of sleep hours/day was 5.97±1.47; 23.8% slept <5 hours; 50.9% made use of alcohol, 95.6% of caffeine, and 11.1% of amphetamines. Mean PSQI was 4.95±2.56; 35.4% had a PSQI >5; 23 subjects snored more than three times a week (11.1%). Mean ESS was 6.56±4.2; 21.7% had a score >10. In the preceding five years, 27 drivers (13.1%) were involved in accidents, 5 of which resulted in injuries and 3 in deaths. CONCLUSION: Results showed a high prevalence of sleep disorders, use of alcohol and psychostimulant drugs, and accidents. OBETIVO: Avaliar a qualidade do sono, trabalho em turnos, consumo de álcool e psicoestimulantes, e a prevalência de acidentes, entre caminhoneiros. MÉTDO: Foram aplicados questionários demográficos, a Escala de Epworth e o Índice de Pittsburgh. A análise estatística foi feita com os testes t de Student, qui-quadrado, Pearson e Fisher. RESULTADOS: 43,2% dirigiam mais que 16 h/dia; 2,9% faziam trabalho por turnos. A média de horas de sono foi 5,97 +/- 1,47. 23,8% dormiam menos de 5 horas. 50,9% faziam uso de bebida alcoólica; usavam cafeína 95,6% e anfetaminas 11,1%. A média do PSQI foi 4,95 +/- 2,56; 35,4% tinham o PSQI maior que 5; 23 sujeitos ressonavam mais que 3 vezes por semana (11,1%). A ESE teve uma média de 6,56 +/- 4,2; 21.7% um escore superior a 10. Nos últimos cinco anos 27 motoristas (13,1%) estiveram envolvidos em acidentes, 5 com feridos e 3 com mortos. CONCLUSÃO: Foi alta a prevalência de distúrbios do sono, uso de álcool e estimulantes, e de acidentes.